2014
DOI: 10.3402/tellusa.v66.24064
|View full text |Cite
|
Sign up to set email alerts
|

Prior history of Mistral and Tramontane winds modulates heavy precipitation events in southern France

Abstract: A B S T R A C T Heavy precipitation events (HPEs) are frequent in southern France in autumn. An HPE results from landward transport of low-level moisture from the Western Mediterranean: large potential instability is then released by local convergence and/or orography. In the upstream zone, the sea surface temperature (SST) undergoes significant variations at the submonthly time scale primarily driven by episodic highly energetic events of relatively cold outflows from the neighbouring mountain ranges (the Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Regarding ocean-atmosphere feedbacks, no sensitivity to the atmosphere-ocean coupling was found on the scaling of precipitation extremes with temperature (not shown). This is not surprising, since atmosphere-ocean feedbacks affect predominantly the location of the precipitating event rather than the intensity Berthou et al 2014Berthou et al , 2015.…”
Section: Simulation Evaluation and Analysismentioning
confidence: 98%
“…Regarding ocean-atmosphere feedbacks, no sensitivity to the atmosphere-ocean coupling was found on the scaling of precipitation extremes with temperature (not shown). This is not surprising, since atmosphere-ocean feedbacks affect predominantly the location of the precipitating event rather than the intensity Berthou et al 2014Berthou et al , 2015.…”
Section: Simulation Evaluation and Analysismentioning
confidence: 98%
“…Most studies of the Western Mediterranean HPEs showed that changes of a few degrees in the upstream SST could modulate precipitation events but in most situations could not drastically change them (Lebeaupin et al 2006;Katsafados et al 2011;Miglietta et al 2011;Berthou et al 2015), except in specific cases: for a squall line on the Balearic islands where SST was determinant in the erosion of an inversion layer ) and a case where the cyclone track was affected and did not land on Calabria anymore (Senatore et al 2014). Lebeaupin Brossier et al (2013) and Berthou et al (2014Berthou et al ( , 2015 showed with regional climate hindcast simulations that HPEs in the Cévennes (southern France) could be modulated by the prior history of Mistral in some cases. However, Berthou et al (2016) showed that cooling of SST by Mistral does not systematically occur before HPEs in the Cévennes.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation field has been evaluated over land against ECA&D (European Climate Assessment and Data set (Haylock et al, 2008)) and SAFRAN (Système d'analyse fournissant des renseignements atmosphériquesà la neige (QuintanaSeguí et al, 2008)) raingauge-based gridded products at the Mediterranean basin scale (Stéfanon et al, 2014;Lebeaupin-Brossier et al, 2013;Flaounas et al, 2013;Berthou et al, 2014Berthou et al, , 2015 and over sea against the satellite product of the Hamburg Ocean Atmosphere Parameters and fluxes from Satellite data (HOAPS) available twice a day with a spatial resolution of 0.5˚in longitude and latitude . AMSU-B/MHS sounders appear as a complementary approach to evaluate the simulation at finer temporal (3-4 h) and spatial (16 km at nadir) resolutions with an homogeneous precipitation information over land and sea.…”
Section: The Weather Research and Forecasting Regional Climate Model mentioning
confidence: 99%